Anion–π and Cation–π Interactions on the Same Surface1. Issue 42 (28th August 2014) - Fujisawa, Kaori; Beuchat, César; Humbert‐Droz, Marie; Wilson, Adam; Wesolowski, Tomasz A.; Mareda, Jiri; Sakai, Naomi; Matile, Stefan
Abstract Herein, we address the question whether anion–π and cation–π interactions can take place simultaneously on the same aromatic surface. Covalently positioned carboxylate–guanidinium pairs on the surface of 4‐amino‐1, 8‐naphthalimides are used as an example to explore push–pull chromophores as privileged platforms for such "ion pair–π" interactions. In antiparallel orientation with respect to the push–pull dipole, a bathochromic effect is observed. A red shift of 41 nm found in the least polar solvent is in good agreement with the 70 nm expected from theoretical calculations of ground and excited states. Decreasing shifts with solvent polarity, protonation, aggregation, and parallel carboxylate–guanidinium pairs imply that the intramolecular Stark effect from antiparallel ion pair–π interactions exceeds solvatochromic effects by far. Theoretical studies indicate that carboxylate–guanidinium pairs can also interact with the surfaces of π‐acidic naphthalenediimides and π‐basic pyrenes.